Faktor-Faktor Yang Memberikan Kontribusi Pada Affective Resident Commitment Warga Kota Bandung - Adella Nilam Ayu Anjani; Yadi Ernawadi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The Indonesia Most Livable City Index assessment for Bandung City of 71 in 2022 is ranked 6th out of 25 top tier cities in Indonesia. The purpose of this study is to examine the effect of place image on affective resident commitment mediated by place attachment of Bandung residents. The survey method with convenience sampling technique was used to determine a sample of 120 respondents. The data analysis technique used is structural equation modeling (SEM) using SmartPLS version 3.0. Of the thirteen research hypotheses proposed, seven of them are supported by empirical data. The results showed that physical appearance and ambient and community service were found to have a positive effect both directly and indirectly on affective resident commitment. The results of this study are expected to provide benefits for further research and the Bandung City government regarding the design of strategies relevant to improving the quality of these attributes.